Fungsi Kepemimpinan Kepala Dinas terhadap Kebijakan Pelayanan Dinas Pengelolaan Sampah, Pertamanan dan Pemakaman Kota Sukabumi - Winda Sulastri (BUANA INFORMATIKA CBI, 2017)
The purpose of this study is to determine the function of the leadership of department heads and public service policies at the Department of Solid Waste Management , and Funeral Sukabumi. The results showed that the Head of Department has been carrying out its functions are implemented through the policy in terms of public services in their work environment . The data used in this study consists of two types of data are primary data and secondary data . Primary data came from staff at the Department of Hygiene and Sukabumi. The secondary data in the form of theories regarding the function of leadership and public service policies obtained from the literature such as books and the internet . This research was conducted at the Department of Hygiene in Jalan Pemuda 1 street No. 71 Sukabumi city. Research with qualitative methods , sampling is purposive and snomball , as well as collection techniques by triangulation , data analysis is inductive / qualitative . Keywords: Function leadership, public service,